Supplementary data to 'Health-motivated taxes on red and processed meat: a modelling study on optimal tax levels and associated health impacts' by Springmann and colleagues - Springmann, M (University of Oxford, 2018)
The file contains results of the impacts of health-motivated taxation of red and processed meat on prices, consumption, attributable deaths, health-care costs, and tax revenue by region, year, and taxing scheme.